Kajian Impelementasi Pembagian Urusan Pemerintahan di Kota Bandung - Anwaruddin, Awang (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
The government policy on the local autonomy based on the Law No.22 year 1999 and then the Law No. 32 year 2003 has been implemented all around Indonesia for about five years during which various attached regulations have been carried out. Among others, the regulation on the government issue distribution is of significance as it will result on the design of organizational structure of local government. However, not all local government have been implemented the regulation because of various reason. This paper is an attempt at avaluating the implementation of the regulation in the city government of Bandung, based on the empirical observations and study on related references. To sum up, a policy recommendation will be proposed to be taken into consideration for the revision of the regulation.